Public Management : Organizations, Governance, and Performance - O'Toole, Laurence J.; Meier, J. Kenneth; Meier, Kenneth J. (New York : Cambridge University Press, 2011)
"How effective are public managers as they seek to influence how public organizations deliver policy results? How, and how much, is management related to the performance of public programs? What aspects of management can be distinguished? Can their separable contributions to performance be estimated? The fate of public policies in today's world lies in the hands of public organizations, which in turn are often intertwined with others in latticed patterns of governance. Collectively, these organizations are expected to generate performance in terms of policy outputs and outcomes. In this book, two award-winning researchers investigate the effectiveness of management in the public sector. Firstly, they develop a systematic theory on how effective public managers are in shaping policy results. The rest of the book then tests this theory against a wide range of evidence, including a data set of 1,000 public organizations"--
Machine generated contents note: List of figures; List of tables; Preface; 1. Public management and performance: an evidence-based perspective; 2. A model of public management and a source of evidence; 3. Public management in interdependent settings: networks, managerial networking and performance; 4. Managerial quality and performance; 5. Internal management and performance: stability, human resources and decision making; 6. Nonlinearities in public management: the role of managerial capacity and organizational buffering; 7. Public management in intergovernmental networks: managing structural networks and managerial networking; 8. Public management and performance: what we know, and what we need to know; Glossary; References; Index.
Keywords: Public management; Administrative agencies -- Management